Multi-gene panel testing and association analysis in Cypriot breast cancer cases and controls - Zanti, Maria; Loizidou, Maria A.; O’Mahony, Denise G.; Dorling, Leila; Dennis, Joe; Devilee, Peter; Easton, Douglas F.; Panayiotidis, Mihalis I.; Hadjisavvas, Andreas; Michailidou, Kyriaki (Frontiers in Genetics, 2023)
Introduction: It is estimated that around 5% of breast cancer cases carry pathogenic variants in established breast cancer susceptibility genes. However, the underlying prevalence and gene-specific population risk estimates in Cyprus are currently unknown. Methods: We performed sequencing on a population-based case-control study of 990 breast cancer cases and 1094 controls from Cyprus using the BRIDGES sequencing panel. Analyses were conducted separately for protein-truncating and rare missense variants. Results: Protein-truncating variants (PTVs) in established breast cancer susceptibility genes were detected in 3.54% of cases and 0.37% of controls. Protein-truncating variants in BRCA2 and ATM were associated with a high risk of breast cancer, whereas PTVs in BRCA1 and PALB2 were associated with a high risk of estrogen receptor (ER)-negative disease. Among participants with a family history of breast cancer, PTVs in ATM, BRCA2, BRCA1, PALB2 and RAD50 were associated with an increased risk of breast cancer. Furthermore, an additional 19.70% of cases and 17.18% of controls had at least one rare missense variant in established breast cancer susceptibility genes. For BRCA1 and PALB2, rare missense variants were associated with an increased risk of overall and triple-negative breast cancer, respectively. Rare missense variants in BRCA1, ATM, CHEK2 and PALB2 domains, were associated with increased risk of disease subtypes. Conclusion: This study provides population-based prevalence and gene-specific risk estimates for protein-truncating and rare missense variants. These results may have important clinical implications for women who undergo genetic testing and be pivotal for a substantial proportion of breast cancer patients in Cyprus.